Can we foster pre-service teachers’ competences for digital collaboration? - Ohle-Peters, Annika; Ludewig, Ulrich; McElvany, Nele (Frontiers in Education, 2024)
Digital collaboration in schools is becoming increasingly important in educational processes—for teachers as well as for students. Teachers’ competences, including professional knowledge (e.g., technological-pedagogical content knowledge; TPCK), attitudes (e.g., regarding the usefulness of digital collaboration), and their motivational orientations (e.g., intrinsic motivation and self-efficacy beliefs), are essential prerequisites for digital collaboration within the teaching staff and for teaching students how to learn collaboratively using digital media. Teacher education at universities plays a crucial role in the development of teachers’ professional competences, yet little is known about how teachers’ digital collaboration competences can be fostered effectively. Hence, the research aim was to investigate (a) the development of pre-service teachers’ TPCK, attitudes, and motivational orientations toward digital collaboration in general, (b) analyze the development of their intentions to use digital collaboration in the future, and (c) evaluate the effectiveness of interventions focused on digitally collaborative learning. In this multi-cohort quasi-experimental study with pre-post design, N = 439 students participated either in intervention group (IG) courses (nIG = 351) explicitly fostering digital collaboration or in regular university courses without explicit fostering of digital collaboration, who served as a control group (CG; nCG = 88). Results of conditional latent three-level growth models indicate a positive development of pre-service teachers’ TPCK and their intentions to use digital collaboration. This research contributes to the highly relevant question of how to prepare teachers for increasingly digitalized teaching and learning settings in school.